2016
DOI: 10.1186/s12974-016-0594-7
|View full text |Cite
|
Sign up to set email alerts
|

STIMs and Orai1 regulate cytokine production in spinal astrocytes

Abstract: BackgroundOur previous study demonstrated that a store-operated calcium channel (SOCC) inhibitor (YM-58483) has central analgesic effects. However, the cellular and molecular mechanisms of such effects remain to be determined. It is well-known that glial cells play important roles in central sensitization. SOC entry (SOCE) has been implicated in many cell types including cortical astrocytes. However, the role of the SOCC family in the function of astrocytes has not been determined. Here, we thoroughly investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 49 publications
(54 reference statements)
3
46
1
Order By: Relevance
“…We and others have shown that YM-58483, a SOC inhibitor, attenuates acute, and chronic pain ( Gao et al, 2013 ; Qi et al, 2016 ). Our previous studies have also demonstrated that SOCs are expressed and functional in spinal cord dorsal horn neurons and astrocytes ( Xia et al, 2014 ; Gao et al, 2016 ). To better understand how SOCs are involved in the pain process, we examined the SOC family expression in DRGs.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We and others have shown that YM-58483, a SOC inhibitor, attenuates acute, and chronic pain ( Gao et al, 2013 ; Qi et al, 2016 ). Our previous studies have also demonstrated that SOCs are expressed and functional in spinal cord dorsal horn neurons and astrocytes ( Xia et al, 2014 ; Gao et al, 2016 ). To better understand how SOCs are involved in the pain process, we examined the SOC family expression in DRGs.…”
Section: Resultsmentioning
confidence: 91%
“…These findings suggest that SOCs play both central and peripheral roles in chronic pain. Although characteristics of SOCs have been established in spinal cord neurons and astrocytes ( Xia et al, 2014 ; Gao et al, 2016 ), the molecular components of SOCs that mediate SOC entry (SOCE) in dorsal root ganglion (DRG) neurons remain elusive. While a previous study has suggested that Orai1 may be involved in SOCE in DRG neurons ( Gemes et al, 2011 ), a recent report has indicated that TRPC3 also contributes to SOCE in DRG neurons ( Alkhani et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primary mouse astrocytes were prepared as previously described [ 47 ] with minimal modification. Briefly, the spinal cord was isolated from neonatal (P1–P2) mice.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a recent study has revealed in spinal cord astrocytes that STIM2 participates in lipopolysaccharide (LPS)‐induced cytokine production (Gao et al . ). STIM2 knockdown significantly reduces SOCE and LPS‐induced interleukin (IL)‐6 and tumour necrosis factor α (TNF‐α) production, cytokines that are involved and upregulated in pain hypersensitivity (Gao et al .…”
Section: Introductionmentioning
confidence: 97%
“…STIM2 knockdown significantly reduces SOCE and LPS‐induced interleukin (IL)‐6 and tumour necrosis factor α (TNF‐α) production, cytokines that are involved and upregulated in pain hypersensitivity (Gao et al . ).…”
Section: Introductionmentioning
confidence: 97%